Implementing a scoping review to explore sport officials' mental health - Carter, Tori B.; Gorczynski, Paul; Coady, Christopher J.; Cunningham, Ian J.; Mascarenhas, Duncan R. D.; Grant, Murray; Sullivan, Philip; Webb, Tom; Livingston, Lori A.; Hancock, David J. (Frontiers in Sports and Active Living, 2024)
Introduction Sport officials are tasked with applying rules, maintaining fairness, and ensuring athlete safety. However, sport officials experience anxiety, burnout, and non-accidental violence, with the incidence of these events increasing worldwide. This has led to rising attrition rates among sport officials, with many sport organizations concerned for their operational capacity. The effects of anxiety, burnout, and non-accidental violence might contribute to or be indicative of sport officials' negative mental health outcomes. To develop a clear understanding of how sport officials' mental health is affected by their occupation, it is necessary to identify the mental health outcomes and predictors they experience, and to what extent. The purpose of this scoping review was to identify and examine the empirical research and policy documents surrounding sport officials' mental health. Method One thousand, two hundred six articles were identified across four databases: PubMed, Web of Science, SportDiscus, and PsycINFO. Next, a policy search was conducted on the respective international governing body websites from English-speaking countries for the 60 included sports. Following screening, 18 studies and one policy document met the inclusion criteria for exploring sport officials' mental health. Results Participants (N = 7,941) in the studies were mainly European male soccer and basketball referees. Most studies utilized quantitative inquiry (n = 15) rather than qualitative methods (n = 2) or framework development (n = 1). The research demonstrated that sport officials frequently experienced negative mental health outcomes and predictors including anxiety, depression, burnout, lower mental health literacy, and high levels of stigmatization towards mental health. Discussion These outcomes were influenced by gender/sex, age, and experience. There is a need to explore personal and environmental (including occupational) factors that cause or contribute to sport officials' mental health symptoms and disorders.